2020
DOI: 10.1002/pen.25514
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid bacterial cellulose‐collagen membranes production in culture media enriched with antioxidant compounds from plant extracts

Abstract: Bioactive, structural, and mechanical properties were measured of a cellulose biopolymer produced by Gluconacetobacter xylinus using hydrolyzed collagen and phenolic compounds from teas and grape pomace (GP) in an optimized culture medium. Biopolymers were impregnated with an antibiotic to investigate possible antibacterial activities. Hybrid bacterial cellulose (BC)-collagen membranes obtained from cultures with green tea and a ternary mixture (TM) of teas with GP presented a high concentration of phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
1
7
1
Order By: Relevance
“…Moradian et al obtained similar results on the antioxidant activity of bacterial cellulose membrane with rosemary extracts at two concentrations (25 and 50%) and similarly, the antioxidant activity significantly increased with increasing concentration of the extracts [17]. Fernandes et al reported a high concentration of phenolic compounds and antioxidant activity of cellulose membranes containing grape pomace [13]. Taokaew et al determined the total polyphenol content of BC films containing ethanolic mangosteen peel extract ranged from 2.06 to 248.20 mg GA/l of dried film [26].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Moradian et al obtained similar results on the antioxidant activity of bacterial cellulose membrane with rosemary extracts at two concentrations (25 and 50%) and similarly, the antioxidant activity significantly increased with increasing concentration of the extracts [17]. Fernandes et al reported a high concentration of phenolic compounds and antioxidant activity of cellulose membranes containing grape pomace [13]. Taokaew et al determined the total polyphenol content of BC films containing ethanolic mangosteen peel extract ranged from 2.06 to 248.20 mg GA/l of dried film [26].…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, topical application of BC enriched with antioxidant components contained in plants seems to be an interesting option. The incorporation of natural active ingredients into BC can be used for topical regeneration and skincare [13,16]. The penetration of antioxidant substances deep into the skin or their accumulation in the skin also plays an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design of experiment (DoE) is a multipurpose statistical tool for optimal formulation and has been widely applied in the industrial sectors of pharmaceutics, biomedicine, cosmetics, textile, food, and agriculture 16,31,39,45–49 . Herein, DoE was applied to optimize the biosynthesis of KBC from dairy industrial wastes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Polymer modification is an efficient method for improving or adding structural and chemical characteristics to BC films, [9] providing antimicrobial, conductive, magnetic, optical, and other properties. [16] Studies have reported polymer modifications through additive formulations, which can be done in two ways: in situ (during membrane formation) [15,16] or ex situ (after the membrane has already been formed). [7] Such methods are used to provide antimicrobial activity, [6] antioxidant activity, [15,17] and healing properties.…”
mentioning
confidence: 99%